Association of Lower Extremity Somatosensation Deficit with Balance and Gait in Sub-Acute Stroke Patients - Sana Arif, Iram Shafee, Nishat Riaz, Isbah Waris, Memoona Hayat, Muhammad Nauman Jamal, Sadaf Waris, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A stroke occurs when the blood supply to part of your brain is interrupted or reduced, preventing brain tissue from getting oxygen and nutrients. There are three types of stroke ischemic stroke hemiplegic stroke and transient ischemic stroke. Objective: To determine the association of lower extremity somatosensory deficit in balance and gait in sub-acute stroke patients. Methods: Cross sectional survey was used in this study. The age group of participants was 40 to 75 years. Sample size was 204 calculated from Rao software and non-probability convenient sampling technique was used. Data was collected from Lahore General Hospital. Data was obtained from patient by applying distal proprioception test to assess the joint position sense. For the assessment of two point discrimination bolay gauge was used. The cutaneous vibration sensation was assessed through tuning fork. Soft goat hair brush was used to check the light touch pressure. For balance assessment berg balance scale and time up and go test was used. Gait was observed through Wisconsin gait index. Results: Mean value and standard deviation of age of participants were 62.99and 6.592 respectively. There was association of berg balance scale with two point discrimination test, light touch pressure and distal proprioception. There was no association between berg balance scale and vibration sense. Mean value and standard deviation of Wisconsin gait index was 23 and 4.986 respectively. Association between TUG and two point discrimination was found. There was no association of TUG with vibration sense, distal proprioception test and light touch pressure. Conclusion: This study concluded that balance was affected in sub-acute stroke patients due to the somatosensory deficit. Fall risk increased in the sub-acute stroke patient as the patients performance measured in time up and go test and berg balance scale. It was also inferred that while patients performing Wisconsin gait index scale, gait was affected in sub-acute stroke patients. Keywords: Balance, Gait, Sub-acute Stroke, fall risk, Somatosensory, Lower extremity